Effect of lipid-lowering treatment in cardiovascular disease prevalence in familial hypercholesterolemia. (May 2019) - Perez-Calahorra, Sofía; Laclaustra, Martín; Marco-Benedí, Victoria; Lamiquiz-Moneo, Itziar; Pedro-Botet, Juan; Plana, Núria; Sanchez-Hernandez, Rosa M.; Amor, Antonio J.; Almagro, Fátima; Fuentes, Francisco; Suarez-Tembra, Manuel; Civeira, Fernando; et al.
Abstract: Background and aims: The impact on heterozygous familial hypercholesterolemia (HeFH) health led by high-intensity lipid-lowering therapy (HILLT) is unknown, and the question remains if there is still an unacceptably high residual risk to justify treatment with new lipid-lowering drugs. Methods: This observational, retrospective, multicenter, national study in Spain, whose information was obtained from a national dyslipemia registry, was designed to establish the current prevalence of cardiovascular disease (CVD) in HeFH and to define the impact of HILLT on CVD in this population. Odds were estimated using several logistic regression models with progressive adjustment. Results: 1958 HeFH, mean age 49.3 ± 14.3 years, were included in the analysis. At inclusion in the registry, 295 patients (15.1%) had suffered CVD and 164 (55.6%) had suffered the first event before the onset lipid-lowering treatment. Exposition to treatment associated more than ten times lower odds for CVD than in subjects naïve to treatment (OR 0.085, 95% CI 0.063–0.114, p < 0.001). A first CVD event after a mean treatment period of 9.1 ± 7.2 years occurred in 131 out of 1615 (8.1%) HeFH subjects, and 115 (87.8%) of them were on HILLT. Conclusions: Current prevalence of CVD among HeFH is one third of that reported before the statins era. Early initiation and prolonged lipid-lowering treatment was associated with a reduction in CVD. New cases of CVD, in spite of HILLT, appeared mostly among patients accumulating risk factors and probably they may be considered for further lipid-lowering drugs. Graphical abstract: Image 1 Highlights: Statins have changed the natural history of cardiovascular disease (CVD) in heterozygous familial hypercholesterolemia (HeFH). We report the current CVD prevalence in HeFH after an average of 9.7 years of statins. 10% of HeFH suffered a CVD event after more than 12 years of statin treatment. HeFH at high risk with high-intensity statins are those with >3 risk factors. This study identifies HeFH patients susceptible for more intensive treatment.